TRANSISI KAUM MUDA MARGINAL DAN REPRODUKSI KELAS SOSIAL - Oki Rahadianto Sutopo (UNIVERSITAS SEBELAS MARET (UNS), 2023)
This article examines school to work transition among marginalized youth in Central Java, Indonesia in the contemporary neoliberal era. We apply Bourdieusian approach as a tool of analysis to cover both material-objective and cultural-subjective dimensions of social class in the phenomenon of youth transition. This research applies qualitative method and data was collected via in-depth interviews, observations and Focus Group Discussions in 2018. This article shows how class as an existing condition of inequality manifested in unequally distributed economic, cultural and social capital effect on the inability of young people to follow the changing rule of the game in the new normality of works. Despite young people tried to negotiate this complex condition using their on-hand stock of social capital; their job option still represents the working-class background. Thus, narrative of marginalized youth transition in the neoliberal era shows how their position are not moving from their original and embedded social background as a working class. Keywords: Youth Transition, Social Class, Bourdieu, Habitus. Abstrak: Artikel ini membahas mengenai transisi kaum muda marginal menuju dunia kerja di Jawa Tengah, Indonesia dalam era neoliberal kontemporer. Pendekatan Bourdieusian diaplikasikan untuk mempertajam analisis baik pada dimensi material-objektif maupun kultural-subjektif kelas sosial dalam transisi kaum muda menuju dunia kerja. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data melalui wawancara mendalam, observasi dan Focus Group Discussion (FGD) pada tahun 2018. Temuan penelitian menunjukkan bagaimana kelas sosial sebagai kondisi awal kesenjangan termanifestasi dalam tidak meratanya persebaran kapital ekonomi, budaya dan sosial yang berimplikasi pada praktik kaum muda yang tidak dapat mengikuti aturan main dalam normalitas baru di ranah kerja. Meskipun mereka mencoba bernegosiasi mengandalkan jejaring sosial, namun pekerjaan didapatkan tidak beranjak dari jenis pekerjaan yang merepresentasikan kelas sosial bawah. Narasi transisi kaum muda marginal menuju dunia kerja menunjukkan bagaimana mereka tidak banyak beranjak dari posisi kelas sosial asal yang melekat sejak mereka dilahirkan. Kata Kunci: Transisi Kaum Muda, Kelas Sosial, Bourdieu, Habitus.